New Light Shed on Chinese Word Segmentation in MT by a Language Investigation - Wu, Zhijie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThe Chinese language, unlike some western languages, is written without a space between any two words, which presents itself as a unique problem in Machine Translation: how to segment words in Chinese? The current word-segmentation systems in Machine Translation are either linguistically-oriented or statistically-oriented. Both types, however, have some innate defects that cannot be overcome due to the pragmatically-oriented feature of the Chinese language. This research aims at addressing the problem of Chinese word segmentation of Machine Translation in light of a language investigation consisting of two surveys and eight interviews.